Secret-sharing with a class of ternary codes - Kohel, David R. (2013)
Secret-sharing is an important topic of cryptography and has applications in information security. One approach to the construction of secret-sharing schemes is based on error-correcting codes. In this paper, we describe a secret-sharing scheme based on a class of ternary codes (Ding et al. IEEE Trans. Inform. Theory IT-46 (2000) 280–284). We determine the access structure and prove properties of the secret-sharing scheme.